PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. RAMAJAYA PRAMUKTI KABUPATEN KAMPAR - Sri Defi Gultom; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted by PT. Ramajaya Pramukti Kampar Regency is located in the Tapung sub-district, Kampar Regency. This study aims to determine the effect of supervision and work discipline on the performance of employees of the production division of PT. RamaJaya Pramukti, Kampar Regency.        In this research, the method used is quantitative descriptive with SPSS 17 program. The sample in this study were all employees of the production division of PT. Ramajaya Pramukti Kampar Regency, amounting to 60 people. Methods of data collection using observation and questionnaires (questionnaire). Hypothesis testing uses multiple linear analysis methods with the results of the study: Y = = 7,774 + 0.486X1 + 0.178X2.       The research that has been conducted shows that the respondents' responses to supervision, work discipline and employee performance are in good categories. As for the (t) test that has been conducted, it shows that the variables of supervision and work discipline partially have a significant effect on employee performance. And the results of the F test show that simultaneously supervision and work discipline for the calculation of the coefficient of determination (R2) obtained R Square value of 0.432 on employee performance. This shows that supervision and work discipline have an effect of 43.2% on employee performance, while the remaining 56.8% is influenced by other variables not examined in this study. Keywords: Supervision, Work Discipline, Employee Performance